2018
DOI: 10.1002/adem.201800166
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Graphene Foam and Graphene Foam—Tissue Composites

Abstract: Graphene foam (GF), a 3-dimensional derivative of graphene, has received much attention recently for applications in tissue engineering due to its unique mechanical, electrical, and thermal properties. Although GF is an appealing material for cartilage tissue engineering, the mechanical properties of GF – tissue composites under dynamic compressive loads have not yet been reported. The objective of this study was to measure the elastic and viscoelastic properties of GF and GF-tissue composites under unconfined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
(96 reference statements)
0
25
0
Order By: Relevance
“…Pristine 3D graphene scaffold with high conductivity can be prepared through synthesizing multilayer graphene on 3D sacrificial nickel template via CVD method . After removing the template, the graphene frameworks can inherit the interconnected and porous structure of the nickel foam.…”
Section: Fabrication Of Graphene Based Scaffolds In Various Dimensionsmentioning
confidence: 99%
“…Pristine 3D graphene scaffold with high conductivity can be prepared through synthesizing multilayer graphene on 3D sacrificial nickel template via CVD method . After removing the template, the graphene frameworks can inherit the interconnected and porous structure of the nickel foam.…”
Section: Fabrication Of Graphene Based Scaffolds In Various Dimensionsmentioning
confidence: 99%
“…28-32 Our graphene foams exhibit wrinkles on the order of several nanometers to 10s of nanometers in good agreement with previous studies. 17,49,107 Furthermore, previous studies have shown the importance of surface functionalization on cell culture. 108-110 While we have focused on the impact of protein functionalization of graphene – cell interfaces, further investigations are needed to better understand the time-dependent biochemical nature of such interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Following the functionalization, GF scaffolds were conditioned for 24 hours in cell culture medium. 49…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As novel porous materials with self‐supporting structure, bulk 3D graphene aerogel can eliminate the common issue of dispersion in the matrix to fully exhibit the reinforcing effect. It has attracted much attention due to their properties of lightweight and good mechanical performance . Glutaraldehyde, gelatin, polyethylenimine, proanthocyanidins, hydrothermal, folding, and physical assembling have been used as versatile cross‐linking agents and methods to assemble graphene nanosheets to 3D structure.…”
Section: Introductionmentioning
confidence: 99%